The changeable political map of the Upper Adriatic region: from conflict to harmony - Bufon, Milan (Revija za geografijo, 2008)
The paper will present a geopolitical and political geographical overview of the Upper Adriatic region as an area of contact between different cultural, social, economic and political entities, producing potential of conflicts, particularly in the period of growing nationalism and emerging nation-state formulation in this region.
Keywords: Upper Adriatic; political geographical transformations; cross-border cooperation; social and spatial convergence and divergence